Grafting Causes Physiological Changes and Promotes Adventitious Root Formation in Rejuvenated Soft Shoots of Taxodium hybrid ‘Zhongshanshan’ - Zhiquan Wang; Qin Shi; Peipei Chen; Feng Sun; David Creech; Zhiguo Lu; Yunlong Yin; Chaoguang Yu (Plants, 2023)
Taxodium hybrid ‘Zhongshanshan’ has been widely used as a timber tree in river network areas and coastal regions and is mainly propagated by cuttings. However, when trees age, their capacity to form adventitious roots becomes weaker. We successfully enhanced the rooting ability of shoots in T. hybrid ‘Zhongshanshan 302’ by their rejuvenation based on grafting. We recorded temporal variation in endogenous auxin, abscisic acid (ABA), gibberellins (GAs), trans-zeatin-riboside (TZR), soluble sugar and H2O2 after root induction. Auxin, soluble sugars and H2O2 levels were higher in rejuvenated shoots than in mature shoots, whereas the opposite was true for ABA and GAs. Notably, indole-3-acetic acid (IAA) and GA3 presented higher contents with more obvious differences in T. hybrid ‘Zhongshanshan 302’ rejuvenated shoots vs. mature shoots compared with other kinds of auxin and GAs. The evident improvement in the rooting ability of rejuvenated shoots after grafting likely resulted from the differential regulation of plant hormones, carbohydrates and redox signaling. In addition to the physiological basis of improved rooting ability by grafting, this study provided a theoretical basis for the optimization of subsequent propagation techniques in T. hybrid ‘Zhongshanshan’ and potentially other Taxodium spp.